INVESTIGATING THE NANODOMAIN ORGANIZATION OF RHODOPSIN IN NATIVE MEMBRANES BY ATOMIC FORCE MICROSCOPY - Senapati, Subhadip (Methods Mol Biol, 2019)
Membrane proteins play an integral role in cellular communication. They are often organized within the crowded cell membrane into nanoscale domains (i.e., nanodomains), which facilitates their function in cell signaling processes. The visualization of membrane proteins and nanodomains within biological membranes under physiological conditions presents a challenge and is not possible using conventional microscopy methods. Atomic force microscopy (AFM) provides an opportunity to study the organization of membrane proteins within biological membranes with sub-nanometer resolution. An example of a membrane protein organized into nanodomains is rhodopsin. Rhodopsin is expressed in photoreceptor cells of the retina and upon photoactivation initiates a series of biochemical reactions called phototransduction, which represents the first steps of vision. AFM has provided an opportunity to directly visualize the packing of rhodopsin in native retinal membranes and the quantitative analysis of AFM images is beginning to reveal insights about the nanodomain organization of rhodopsin in the membrane. In this report, we outline procedures for imaging rhodopsin nanodomains by AFM and the quantitative analysis of those AFM images.